2018
DOI: 10.1016/j.jjcc.2017.09.002
|View full text |Cite|
|
Sign up to set email alerts
|

The Selvester QRS score as a predictor of cardiac events in nonischemic dilated cardiomyopathy

Abstract: The Selvester QRS score can predict future cardiac events in NIDCM, reflecting myocardial fibrosis assessed by CVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
1
19
0
4
Order By: Relevance
“…
Heart failure (HF) is a progressive systemic disease and a major public health problem in developed countries [1]. Despite modern progress in medical management, HF remains a common cause of recurrent hospitalization or death, and a number of prognostic predictors of HF have been reported, including age, New York Heart Association (NYHA) functional class, HF admission, clinical history of hypertension or chronic obstructive pulmonary disease, etiology of cardiomyopathy, blood pressure, brain natriuretic peptide (BNP) level, and parameters of echocardiography or electrocardiogram [2,3]. On the other hand, HF is a systemic clinical syndrome with multiple impaired organs due to low perfusion and congestion
…”
mentioning
confidence: 99%
“…
Heart failure (HF) is a progressive systemic disease and a major public health problem in developed countries [1]. Despite modern progress in medical management, HF remains a common cause of recurrent hospitalization or death, and a number of prognostic predictors of HF have been reported, including age, New York Heart Association (NYHA) functional class, HF admission, clinical history of hypertension or chronic obstructive pulmonary disease, etiology of cardiomyopathy, blood pressure, brain natriuretic peptide (BNP) level, and parameters of echocardiography or electrocardiogram [2,3]. On the other hand, HF is a systemic clinical syndrome with multiple impaired organs due to low perfusion and congestion
…”
mentioning
confidence: 99%
“…1b ) were also detected in 5/6Nx wild-type mice. Inflammatory cytokines and fibrosis-related factors underlie CKD-induced heart failure 33 , 34 . The mRNA levels of inflammatory cytokines interleukin-6 ( IL-6 ) and tumor necrosis factor-α ( Tnf α) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, which yielded comparable results to ours, evaluated the diagnostic performance of the QRS scores in various events among HF subjects. The mean QRS score in nonischemic dilated cardiomyopathy patients was reported as 4.2 points by Hiraiwa et al [13]. Wieslander et al [14] showed that SSc was a strong predictor of LV remodeling (echocardiographic) than clinical outcomes in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the capability of SSc as prognostic markers for cardiac events in different clinical entities (including ST elevation myocardial infarction, aortic stenosis, nonischemic dilated cardiomyopathy), by reflecting the amount of myocardial fibrosis [7,9].…”
Section: Introductionmentioning
confidence: 99%